Minimally Invasive Management of Traumatic Oral Fibroma in Pediatric Patient - Erin Imaniar Basar Erin Imaniar Basar; Varellia Awang Wangi Kardikadewi Varellia Awang Wangi Kardikadewi; Tania Saskianti Tania Saskianti; Sindy Cornelia Nelwan Sindy Cornelia Nelwan (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2026)
Introduction: Oral traumatic fibroma is a benign reactive lesion resulting from mechanical irritation or trauma, characterized by an overproduction of fibrous connective tissue within the oral mucosa. Standard management of traumatic fibroma typically involves surgical excision. However, in pediatric patients, surgical procedures may present challenges due to the potential for procedural anxiety associated with sharp instruments and pain. Purpose: This case reporting and highlighting non-invasive therapy for the management of oral traumatic fibroma in children. Case description: A 13-year-old girl presented to dental hospital with complaints of swelling and ulceration on the left lower labial mucosa and the left dorsum of the tongue, following a traffic accident that occurred two weeks earlier. Treatment included debridement, removal of irritating factors, and the patient was prescribed topical coating agent. The patient is scheduled for close monitoring and observation of oral traumatic fibroma. A significant reduction in lesion size was observed. The patient demonstrated high compliance and satisfaction with the treatment process. Conclusion: Minimally invasive treatment presents a viable and well-tolerated option for managing oral traumatic fibroma in pediatric patients. This method can successfully reduce the lesion's size without requiring invasive procedures.